In-containment hydrogen behavior simulation and hydrogen concentration control under LBLOCA accidents - Tianfan, Wu; Feng, Xue; Shuo, Ding; Li, Wang; Wanai, Li; Yifan, Wang (Frontiers in Energy Research, 2022)
During a design basis accident in a pressurized water reactor (PWR), the released hydrogen through reactor breaks would induce the hydrogen detonation. The hydrogen passive autocatalytic recombiner (PAR) is widely used as a hydrogen elimination measure in nuclear power plants due to its passive capability, low starting threshold and easy installation. The present work aims to study the hydrogen risk after the occurrence of cold section double-end shear fracture large break loss coolant accident (LBLOCA) by using the 3D computational fluid dynamics program GASFLOW. A full containment model of CPR1000 is built. The hydrogen production rate inside the containment after LBLOCA is calculated from the related physicochemical reactions. The hydrogen transport, hydrogen concentration distribution and temperature distribution inside the containment are simulated. The effects of different roughness of the structure surface on the simulation are investigated, and it is proved that the operation of PAR can control the hydrogen concentration under the safety threshold of 4 vol%. The effects of hydrogen flow rate and PAR’s position on the hydrogen elimination efficiency are studied. Based on these studies, this paper makes some suggestions and theoretical references for the spatial arrangement scheme of PAR in the containment to optimize the hydrogen elimination efficiency.